2021
DOI: 10.1073/pnas.2013894118
|View full text |Cite
|
Sign up to set email alerts
|

Public data from three US states provide new insights into well integrity

Abstract: Oil and gas wells with compromised integrity are a concern because they can potentially leak hydrocarbons or other fluids into groundwater and/or the atmosphere. Most states in the United States require some form of integrity testing, but few jurisdictions mandate widespread testing and open reporting on a scale informative for leakage risk assessment. In this study, we searched 33 US state oil and gas regulatory agency databases and identified records useful for evaluating well integrity in Colorado, New Mexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…This shallow geologic trapping of fugitive gas is beneficial from a climate standpoint, mitigating greenhouse gas emissions to atmosphere but poses greater risk to groundwater resources, if present. Furthermore, most fugitive gas leakage monitoring and detection regulations rely on surface‐focused methods with little emphasis on the identification or quantification of subsurface gas migration (Karion et al., 2013; Lackey et al., 2021). These surface‐based methods will likely not be able to delineate subsurface leakage in regions with surficial geology similar to the WCSB.…”
Section: Discussionmentioning
confidence: 99%
“…This shallow geologic trapping of fugitive gas is beneficial from a climate standpoint, mitigating greenhouse gas emissions to atmosphere but poses greater risk to groundwater resources, if present. Furthermore, most fugitive gas leakage monitoring and detection regulations rely on surface‐focused methods with little emphasis on the identification or quantification of subsurface gas migration (Karion et al., 2013; Lackey et al., 2021). These surface‐based methods will likely not be able to delineate subsurface leakage in regions with surficial geology similar to the WCSB.…”
Section: Discussionmentioning
confidence: 99%
“…The migration of methane (CH 4 ), the primary component of natural gas, into shallow groundwater is the most cited water quality issue associated with UOGD in the Marcellus Shale of Pennsylvania (PA), the largest U.S. shale gas play, and has been noted in other shale gas basins nationwide. , CH 4 leakage typically results from improper well construction (i.e., lacking casings to prevent gas migration from overpressured formations) or well integrity issues (i.e., defective casings or gas migration along the well annulus). Additionally, CH 4 can reach groundwater wells several kilometers away from a leaking UOG well via migration along faults or fractures. , CH 4 is nontoxic and common in shallow groundwater throughout hydrocarbon-bearing basins prior to UOGD due to the ubiquity of microbial methanogenesis and upward migration of thermogenic CH 4 (produced via the thermal maturation of organic matter at depth) over geologic timescales. However, recently migrated CH 4 from leaking UOG wells poses an explosion hazard above 10 mg/L and can induce redox effects that mobilize toxic species (e.g., arsenic) or lead to the formation of toxic compounds (e.g., sulfide). , …”
Section: Introductionmentioning
confidence: 99%
“…36,37 Wells in the GWA have a history with integrity issues�26.5% of wells in the region have exhibited SCP at some point during their lifetime. 28 Review of construction records has shown that excess levels of SCP in older wells that have surface casings too shallow to protect the deepest groundwater aquifer may be a potential source of groundwater contamination in the GWA. 13,31 The release of surface casing gases during SCP testing or venting may also contribute to the elevated emissions of methane and nonmethane hydrocarbons detected from oil and gas operations in the region.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In some jurisdictions, migrated surface casing fluids remain trapped beneath a sealed valve at the wellhead, where they build pressure and can escape into groundwater if left unchecked . Other jurisdictions require operators to leave annular valves open, which releases surface casing gases into the atmosphere, where they contribute to emissions of methane and volatile organic compounds . The relative ease with which sustained casing pressure (SCP) and casing-vent flow (CVF) can be detected and measured makes these observations valuable indicators of well integrity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation